ANALISIS PENERAPAN PRINSIP-PRINSIP LEGAL DRAFTING DALAM PEMBENTUKAN UNDANG-UNDANG NO. 11 TAHUN 2020 TENTANG CIPTA KERJA - Silvia Amalina; Nor Hafizah; Akhmad Zaki Yamani (Yayasan Pendidikan Literasi Borneo, 2026)
The quality, clarity, and legal certainty of legal standards are determined by legal drafting, which is crucial to the creation of legislation. However, there are still a number of obstacles to the use of legal drafting principles in Indonesia, such as ambiguous legislative provisions, inconsistent terminology, and insufficient public participation. This study uses normative legal research with a literature study technique to examine how legal drafting principles are applied in the creation of legislation. Legislation, books, journals, and other pertinent legal sources were used to conduct a descriptive analysis of the data. The findings demonstrate that the principles of legal drafting have not been adequately applied, especially with regard to public participation, legal certainty, clarity, and uniformity.Therefore, strengthening the application of legal drafting principles is necessary to produce legislation that is clear, effective, and provides greater legal certainty